Telemonitoring dan Pengendalian Suhu Kadar Kelembapan serta Intensitas Cahaya Matahari di dalam Ruangan Semi Indoor Menggunakan Sistem Wireless Sensor - Reza Syahrindra; Farida Arinie Soelistianto; Putri Elfa Mas’udia (Politeknik Negeri Malang, 2020)
The room temperature depends on the intensity of light. Low light intensity is not proper for the room because it causes bacteria or fungus on the room’s walls. We create a telemonitoring system and air quality control in semi-indoor rooms using wireless sensors as a support system. It can provide real-time information to the user on the screen display. In this study, we use a wireless sensor as monitoring, VEML6070, DHT11, and BH1750 as sensors to determine the air quality in the semi-indoor room. Data will be sent from Arduino Uno to a server through raspberry pi 3 and NRF24L01. Client-server communication techniques are designed for communication between the node and the server, so the data transmission errors can be pressed. The display of the work system will be monitored using a display in the android application. From the experimental results, the system between the node and the server runs well. The experimental results obtained varying Delay with an average delay of 0.318 seconds when there is no change in conditions on the fan and UV lamp. The average Delay is 0.491 seconds when there is a change in conditions on the fan and UV light